Ferritin as an iron transport protein ferritin uptake and iron ultilisation by guinea pig placenta - Lamparelli, Rosario D. V. (My University, 1990)
The guinea pig clears circulating tissue ferritin in a manner different from other mammals. Previous work in man and in rats has shown that injected tissue ferritin is removed from the plasma predominantly by the liver; however, in the guinea pig it is cleared predominantly by red cell precursors and furthermore, the ferritin iron is utilised directly for haem synthesis. During pregnancy, the foeto-placental complex also has a high requirement for iron.
A dissertation submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg in fulfilment of the Degree of Master of Science in the branch of Medicine
Keywords: Ferritins; Biological Transport; Placenta; Swine